GRAPHIC NOVELS AS LEARNING TOOLS - RAO, RATNA (International Journal of Psychosocial Rehabilitation, 2020)
Graphic novels over the years have become popular and have established themselves as important tools of teaching and learning. These novels not only create interest but also provide ease in learning and analysing because of the visual input. Graphic novels are useful in equipping learners with language skills like reading and writing, vocabulary and mood. Higher Order Thinking skills, media literacy, multiple intelligences can also be developed and enhanced using graphic novels.